Relações de cooperação em consórcios públicos de regiões metropolitanas: análises do CONDIAM/PB e consórcio grande Recife - Nascimento, Alex Bruno Ferreira Marques do (2012)
With the disorganized decentralization occurred in Brazil after the 1988 Constitution, municipalities have risen to the level of federal entities. This phenomenon became known as "municipalism" also brought some negative effects such as low capacity financial, economic and political of these entities. In the face of this reality , the municipalities sought in models of collaborative features to address public policy issues ultrarregionais, one of these models are the Public Consortia. Characterized as the organization of all federal entities that aim to solve public policy implementation alone that they could not, or spend great resources for such. This reality of the municipalities have an aggravating factor when looking at the situation in Metropolitan Regions (MRs). This is because the RMs has a historical process of formation that does not encourage cooperation, since that were created top-down during the military regime. Furthermore, the metropolitan municipalities have significant power asymmetries, localist vision, rigidity earmarked revenues, different scenarios conurbation, difficulty standardization of concepts and others that contribute to the vision of low cooperation of these metropolitan areas. Thus, the problem of this work is in the presence of collaborative arrangements, such as the Public Consortia in metropolitan areas, which are seen as areas of low cooperation. To elucidate this research was used for analysis the cases of CONDIAM/PB and Consórcio Grande Recife/PE, because they are apparently antagonistic, but with some points of similarity. The cases has as foundation the Theory of Common Resources, which provides the possibility of collective action through the initiative of individuals. This theory has as its methodology for analyzing the picture IAD Framework, which proposes its analysis based on three axes: external variables, the arena of action and results. The nature of the method of this research was classified as exploratory and descriptive. For the stage of date analysis, was used the method of document analysis and content, Further than of separation of the cases according to theur especificities. At the end of the study, noted that the CONDIAM/PB was a strategy of municipal government of Joao Pessoa to attract funds from the Federal Government for the purpose of to build a landfill, and over the years the ideology of cooperation was left aside, the prevailing view localist municipalities. In the case of Consórcio Grande Recife/PE, members act with some degree of cooperation, especially the collaborative aspect of the region, however, still prevails with greater strength the power of the state of Pernambuco in the decisions and paths of the consortium. Thus, was conclude that the Public Consortia analyzed are an experience of collaborative arrangement, from the initiative of members, as the theory of common resources says, but has not actually signed as a practice of collective action to overcome the dilemmas faced by metropolitan areas